DINAMIKA UNI EROPA : INTEGRASI KAWASAN DAN REFERENDUM BRITANIA RAYA - Riska Luneto (Universitas Jenderal Ahmad Yani, 2021)
European Union is a form of regional interdependence based on a common identity within a region. The EU as a regional institution and a new actor in international politics has become a party that plays an important role in regional interaction and cooperation. In this paper, the author tries to explain the dynamics of regional cooperation that is formed by the EU based on the concept of regional integration from several perspectives, the existence of a common identity, the need for economic improvement to development are several reasons related to the birth of regional integration. On the one hand, for approximately 60 years the EU has been running, problems have arisen when the UK has held a referendum since 2015, the choice to leave the EU was deemed necessary because Britain faces various problems related to sovereignty, immigrants, and the problems of the crisis that the EU is experiencing.